JBIC Journal of Biological Inorganic Chemistry - Que, Lawrence; Metzler-Nolte, Nils.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
A Publication of the Society of Biological Inorganic Chemistry Objectives and policy of the journal Biological inorganic chemistry is a growing field of science that embraces the principles of biology and inorganic chemistry and impacts other fields ranging from medicine to the environment. JBIC (Journal of Biological Inorganic Chemistry) seeks to promote this field internationally. The Journal is primarily concerned with advances in understanding the role of metal ions within a biological matrix$1 (Bbe it a protein, DNA/RNA, or a cell, as well as appropriate model studies. Manuscripts describing high-quality original research on the above topics in English are invited for submission to this Journal. The Journal publishes original articles, minireviews, and commentaries on debated issues.s
Keywords: Biochemistry; Microbiology; Biochemistry, general; Microbiology